Adipose tissue is prominent in salivary glands of Sjögren's syndrome patients and appears to influence the microenvironment in these organs. (3rd July 2016) - Skarstein, Kathrine; Aqrawi, Lara A.; Øijordsbakken, Gunnvor; Jonsson, Roland; Jensen, Janicke Liaaen
Abstract: A minor salivary gland (SG) biopsy with focal lymphocytic sialadenitis and a focus score of ≥1 is today's widely accepted pathological finding confirming the SG component of Sjögren's syndrome (SS). Adipocytes can occupy a large percentage of the SG area although little is known about their significance in SS lesions. This study aimed to characterise adipose tissue infiltration in labial SG biopsies from 27 SS patients and 28 non-SS sicca controls. Biopsies were evaluated by one oral pathologist and assessed for focus score, acinar atrophy, fatty replacement and non-specific chronic inflammation. Moreover, to explore the SG microenvironment, immunohistochemical staining of paraffin-embedded SG tissue was performed using interleukin-6 (IL-6). The fatty replacement was evident in all SS patients possessing autoantibodies (Ro/SSA and/or La/SSB) as well as a positive SG biopsy (focus score ≥1). Additionally, 62% of SS patients having autoantibodies but a negative biopsy showed fatty infiltration (FI) while non-SS controls demonstrated fatty replacement in only 32% of the cases. Overall, the SS group (mean age 53.0 years) had a significantly higher incidence ( p value 0.005) of FI than the non-SS controls (mean age 54.8 years). Interestingly, adipocytes were located in IL-6 rich areas, and IL-6 positive adipocytes were detected. As fat deposition seems to be more recurrent in SGs affected by SS, we propose the assessment of adipose tissue replacement as a helpful tool for diagnostic evaluation in SS. Detection of IL-6 positive adipocytes suggests their involvement in immune reactions. Still, functional studies are needed to investigate the SG microenvironment further.